The Ideology of Capitalism in The Novel Clara Ng's “Langkah Sejuta Suluh” - Setiani, Adris; Supriyanto, Teguh; Setyaningsih, Nas Haryati (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
One of the novels about capitalism is a novel entitled Langkah Sejuta Suluh by Clara Ng. The main character in the novel has a high spirit of capitalism to achieve success. The main character named Merry managed to change the lower class's fate because his hard work turned into the upper class. This study aims to determine the characteristics of capitalism in the main character in Clara Ng's novel Langkah Sejuta Suluh. The researcher uses a theoretical approach in the form of literary sociology theory and Marx's theory of capitalism, as well as a qualitative descriptive methodological approach. The data collection technique of this research used heuristic techniques. The data analysis technique used is hermeneutic. Researchers used triangulation techniques for data validity, namely different data collection techniques to obtain data from the same source. The analysis results show that (1) the ideological characteristics of the main character in the novel Langkah Sejuta Suluh by Clara Ng are competition (competition) to become the best employee and pursue personal gain. (2) The practice of capitalism ideology in Clara Ng's novel Langkah Sejuta Suluh, Merry works for others and dares to earn money. (3) The social class of the main character, namely Merry, has changed due to his efforts and hard work so that those who were originally from the lower class turned into the upper class. Novel Langkah Sejuta Suluh karya Clara Ng berisi tentang motivasi meraih financial sebelum umur 30 tahun yang merupakan sebuah cerminan dari apa yang ada dalam masyarakat pada masa itu. Hal ini tidak terlepas dari pergulatan utama manusia yaitu kebutuhan untuk memenuhi materialnya. Pergulatan itu membawa manusia berhadapan dengan alam sebagai sumber pemenuhan kebutuhan. Agar kebutuhannya terpenuhi, manusia dituntut untuk melakukan transformasi terhadap alam. Usaha-usaha transformasi tersebut membuahkan teknologi dan hubungan-hubungan sosial. Tujuan penelitian ini adalah menganalisis ciri kapitalisme pada tokoh utama dalam novel Langkah Sejuta Suluh karya Clara Ng. Peneliti menggunakan pendekatan sosiologi sastra dan teori kapitalisme serta pendekatan metodologis deskriptif kualitatif. Teknik pengumpulan data penelitian ini menggunakan teknik heuristik. Peneliti menggunakan teknik trianggulasi sebagai validitas data, yaitu teknik pengumpulan data yang berbeda-beda untuk medapatkan data dari sumber yang sama. Analisis data yang penelitian ini adalah teknik analisis semiotik Lotman dan teknik analisis data dialektik. Hasil analisis penelitian adalah (1) ciri ideologi tokoh utama dalam novel Langkah Sejuta Suluh karya Clara Ng. (2) praktik ideologi kapitalisme dalam novel Langkah Sejuta Suluh karya Clara Ng, dan (3) hubungan ideologi kapitalisme di dalam teks dan di luar teks dalam novel Langkah Sejuta Suluh karya Clara Ng. The novel Step a Million Suluh by Clara Ng contains the motivation to achieve financial success before the age of 30 which is a reflection of what existed in society at that time. This is inseparable from the main struggle of humans, namely the need to fulfill their material needs. This struggle brings humans to face nature as a source of fulfillment of needs. In order for their needs to be fulfilled, humans are required to transform nature. These transformation efforts produce technology and social relations. The purpose of this study is to analyze the characteristics of capitalism in the main character in the novel Step a Million Suluh by Clara Ng. The researcher uses a sociological approach to literature and capitalism theory as well as a qualitative descriptive methodological approach. The data collection technique in this research used heuristic techniques. Researchers used triangulation techniques as data validity, namely different data collection techniques to obtain data from the same source. The data analysis used in this research is Lotman's semiotic analysis technique and dialectical data analysis technique. The results of the research analysis are (1) the ideological characteristics of the main character in the novel Step Sejuta Suluh by Clara Ng. (2) the practice of capitalism ideology in Clara Ng's novel Step Sejuta Suluh, and (3) the relationship between the ideology of capitalism in the text and outside the text in Clara Ng's novel Step Sejuta Suluh.